PET measurement of cyclooxygenase-2 using a novel radioligand: upregulation in primate neuroinflammation and first-in-human study - Shrestha, Stal; Kim, Min-Jeong; Eldridge, Mark; Lehmann, Michael L.; Frankland, Michael; Liow, Jeih-San; Yu, Zu-Xi; Cortes-Salva, Michelle; Telu, Sanjay; Henter, Ioline D.; Gallagher, Evan; Lee, Jae-Hoon; et al. (Journal of neuroinflammation, 2020)
Cyclooxygenase-2 (COX-2), which is rapidly upregulated by inflammation, is a key enzyme catalyzing the rate-limiting step in the synthesis of several inflammatory prostanoids. Successful positron emission tomography (PET) radioligand imaging of COX-2 in vivo could be a potentially powerful tool for assessing inflammatory response in the brain and periphery. To date, however, the development of PET radioligands for COX-2 has had limited success. The novel PET tracer [ C]MC1 was used to examine COX-2 expression [1] in the brains of four rhesus macaques at baseline and after injection of the inflammogen lipopolysaccharide (LPS) into the right putamen, and [2] in the joints of two human participants with rheumatoid arthritis and two healthy individuals. In the primate study, two monkeys had one LPS injection, and two monkeys had a second injection 33 and 44 days, respectively, after the first LPS injection. As a comparator, COX-1 expression was measured using [ C]PS13. COX-2 binding, expressed as the ratio of specific to nondisplaceable uptake (BP ) of [ C]MC1, increased on day 1 post-LPS injection; no such increase in COX-1 expression, measured using [ C]PS13, was observed. The day after the second LPS injection, a brain lesion (~ 0.5 cm in diameter) with high COX-2 density and high BP (1.8) was observed. Postmortem brain analysis at the gene transcript or protein level confirmed in vivo PET results. An incidental finding in an unrelated monkey found a line of COX-2 positivity along an incision in skull muscle, demonstrating that [ C]MC1 can localize inflammation peripheral to the brain. In patients with rheumatoid arthritis, [ C]MC1 successfully imaged upregulated COX-2 in the arthritic hand and shoulder and apparently in the brain. Uptake was blocked by celecoxib, a COX-2 preferential inhibitor. Taken together, these results indicate that [ C]MC1 can image and quantify COX-2 upregulation in both monkey brain after LPS-induced neuroinflammation and in human peripheral tissue with inflammation. ClinicalTrials.gov NCT03912428. Registered April 11, 2019.